Efisiensi Pemasaran Minyak Serai Wangi Sarimbata Di Desa Pinilh Kecamatan Dimembe Kabupaten Minahasa Utara - Hatidja, Natasya Natalia; Loho, Agnes Estephina; Tangkere, Ellen Grace (Sam Ratulangi University, 2024)
This study aims to determine the marketing channels and marketing margins of citronella oil and to determine the marketing efficiency of citronella oil in Pinilih Village, Dimembe District, North Minahasa Regency. This research was conducted from August to November 2023 at the Sarimbata citronella oil business in Pinilih Village, Dimembe District, North Minahasa Regency. The data used is primary data obtained directly from the business owner of Citronella Oil in the form of marketing channel data, product prices and marketing costs, while secondary data is obtained from information data related to this research in the form of supporting data, related literature studies either from research results or journals. Data analysis uses descriptive analysis to explain the real conditions of marketing including producers, and retail traders, institutions that contribute to marketing margin analysis activities. The results showed that the marketing channel for citronella oil follows 2 channels, namely: the first channel is Producers - Retailers - consumers, and the second channel is Producers - Collecting Traders - Retailers - Consumers. The amount of margin from channel 1 specifically for 30 cc packaging is IDR 5,000, while channel 2 specifically for 60 cc packaging is IDR 10,000 for collectors, and IDR 15,000 for retailers. The marketing efficiency of citronella oil in each marketing channel is included in the efficient category, because the EP value is < 50%. In the first marketing channel the EP value is 0.33%, and in the second marketing channel the EP value is 1.07%.